Giving the devil his due Satan and cinema - Weinstock, Jeffrey Andrew 1970-; Hansen, Regina M. (Fordham University Press, 2021)
The first collection of essays to address Satan's ubiquitous and popular appearances in filmLucifer and cinema have been intertwined since the origins of the medium. As humankind's greatest antagonist and the incarnation of pure evil, the cinematic devil embodies our own culturally specific anxieties and desires, reflecting moviegoers' collective conceptions of good and evil, right and wrong, sin and salvation. Giving the Devil His Due is the first book of its kind to examine the history and significance of Satan onscreen. This collection explores how the devil is not just one monster among many, nor is he the "prince of darkness" merely because he has repeatedly flickered across cinema screens in darkened rooms since the origins of the medium. Satan is instead a force active in our lives.